Versatile Platelet Rich Plasma: Various Uses Of It (Journal of Pharmaceutical Negative Results, 2022)
Prior to implant placement, augmentation may be necessary for severely atrophied or edentulous maxilla. As activated platelets release autogenous growth factors (GFs) into the wound healing site, this stimulates healing. Platelet rich plasma (PRP) has been proposed to improve and increase the healing of bone transplants. Numerous methods have been developed over the past few years to enhance the quantity and the quality of bone in preparation for the implantation of oral implants for oral rehabilitation. Autogenous bone is still the benchmark. Platelet-rich plasma is one of the supplementary procedures for bone augmentation. In a publication published in 1998, Marx et al. established this idea for clinical use. In this article, we emphasize on the use of PRP in dental implantology and examine and explain the method of particulate bone and PRP in patients. In addition, we were keen to investigate the early thrombotic events that PRP and whole blood caused on an implant surface as well as the utilisation of PRP to speed up bone repair surrounding dental implants.